2021
DOI: 10.3389/fimmu.2020.622509
|View full text |Cite
|
Sign up to set email alerts
|

Exhausted CD8+T Cells in the Tumor Immune Microenvironment: New Pathways to Therapy

Abstract: Tumor-specific CD8+T cells are exposed to persistent antigenic stimulation which induces a dysfunctional state called “exhaustion.” Though functioning to limit damage caused by immune response, T cell exhaustion leads to attenuated effector function whereby cytotoxic CD8+T cells fail to control tumor progression in the late stage. This pathway is a dynamic process from activation to “progenitor exhaustion” through to “terminally exhaustion” with distinct properties. With the rapid development of immunotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
151
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 191 publications
(179 citation statements)
references
References 95 publications
1
151
0
3
Order By: Relevance
“…T cell exhaustion refers to the loss of T cell functions in patients with common chronic infections and cancer. Patients with cancer normally possess a large number of T cells, but most of them are exhausted (28). We found that CD161 was positively correlated with marker genes of exhausted T cells, immune activating genes, and immunosuppressive genes in pan-cancer such as TIGIT, PDCD1, LAG3, CTLA4, STING1, CD96, and IDO1.…”
Section: Discussionmentioning
confidence: 76%
“…T cell exhaustion refers to the loss of T cell functions in patients with common chronic infections and cancer. Patients with cancer normally possess a large number of T cells, but most of them are exhausted (28). We found that CD161 was positively correlated with marker genes of exhausted T cells, immune activating genes, and immunosuppressive genes in pan-cancer such as TIGIT, PDCD1, LAG3, CTLA4, STING1, CD96, and IDO1.…”
Section: Discussionmentioning
confidence: 76%
“…Indeed, one of the hallmarks of cancer is the functional impairment of T-cells caused by a plethora of suppressive determinants in the TME, which leads to T-cell exhaustion [ 23 , 24 , 25 , 26 , 27 ]. Chronic antigen stimulation in the TME and immunosuppressive cytokines lead to dysfunctional T-cells, which are characterized by a peculiar continuum of epigenetic and transcriptional alterations resulting in the expression of inhibitory receptors and loss of early differentiation markers [ 28 , 29 , 30 , 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…This class of receptors can be targeted through mAbs to restore immune responses in cancer patients, a therapeutic strategy that has led to unprecedented long-term responses in a variety of cancers [ 75 ]. In T cell, expression of immune checkpoints such as PD-1, CTLA-4, TIM-3, TIGIT, or LAG3 is associated with functional exhaustion [ 76 ]. Although some of these receptors have been observed on NK cells, their implications for NK cell functions are only starting to be explored.…”
Section: T Cell-associated Immune Checkpointsmentioning
confidence: 99%